Boosting E-Service Quality through IT Service Management of Online Stores - Sandy Kosasi; Vedyanto Vedyanto; I Dewa Ayu Eka Yuliani (IAES Indonesia Section, 2019)
The intention of conducting such the research was to evaluate mediating roles of IT service management on information system success model and IT governance, further boosting E-service quality. A method combining convergent triangulation and an explanatory, follow-up design was implemented. The population engaged middle-up online stores that have marketed products online in five-year time in West Kalimantan. Questionnaires were completed by 99 out of 112 managers. Quantitative analysis was performed through SEMPLS. In-depth interviews and FGDs with 5 key informants, however, yielded data used for qualitative analysis. Results conclusively reveal that information system success model is insignificant for E-service quality despite direct, positive influences gained. In other words, the business success of online stores has no reliance on this type of model. The focus should be on IT governance reinforcing IT service management. The fact is supported by qualitative findings emphasizing that such the governance is eminently influenced by information system success model and it is requisite to actualize IT service management for progressed E-service quality.